Two interventions for equality in compulsary school: reasons for a contrasted becoming - Fassa, Farinaz; Naef, Céline (Swiss Journal of Educational Research, 2018)
This article analyses two actions that were carried out by the Swiss Equality responsibles: on one hand, the yearly event dedicated since 2001 to vocational choices, (The Girls’ day and the following associated manifestations) and on the other the pedagogical material that was produced by the French speaking Conference of Equality Officers in 2006, L’école de l’égalité. Drawing on the work of Boltanski and Thévenot (1991) on justice, this paper puts into light how institutions do reach an agreement and it examines its normative bases in order to understand the very different becoming of these two actions.